Local climate modulates the development of soil nematode communities after glacier retreat - Alessia Guerrieri; Isabel Cantera; Silvio Marta; Aurélie Bonin; Alexis Carteron; Roberto Ambrosini; Marco Caccianiga; Fabien Anthelme; Roberto Sergio Azzoni; Peter Almond; Pablo Alviz Gazitúa; Sophie Cauvy‐Fraunié; et al. (Global Change Biology, 2024)
The worldwide retreat of glaciers is causing a faster than ever increase in ice‐free areas that are leading to the emergence of new ecosystems. Understanding the dynamics of these environments is critical to predicting the consequences of climate change on mountains and at high latitudes. Climatic differences between regions of the world could modulate the emergence of biodiversity and functionality after glacier retreat, yet global tests of this hypothesis are lacking. Nematodes are the most abundant soil animals, with keystone roles in ecosystem functioning, but the lack of global‐scale studies limits our understanding of how the taxonomic and functional diversity of nematodes changes during the colonization of proglacial landscapes. We used environmental DNA metabarcoding to characterize nematode communities of 48 glacier forelands from five continents. We assessed how different facets of biodiversity change with the age of deglaciated terrains and tested the hypothesis that colonization patterns are different across forelands with different climatic conditions. Nematodes colonized ice‐free areas almost immediately. Both taxonomic and functional richness quickly increased over time, but the increase in nematode diversity was modulated by climate, so that colonization started earlier in forelands with mild summer temperatures. Colder forelands initially hosted poor communities, but the colonization rate then accelerated, eventually leveling biodiversity differences between climatic regimes in the long term. Immediately after glacier retreat, communities were dominated by colonizer taxa with short generation time and r‐ecological strategy but community composition shifted through time, with increased frequency of more persister taxa with K‐ecological strategy. These changes mostly occurred through the addition of new traits instead of their replacement during succession. The effects of local climate on nematode colonization led to heterogeneous but predictable patterns around the world that likely affect soil communities and overall ecosystem development.